PERAN KELUARGA DALAM MEMBENTUK IDENTITAS KRISTIANI PADA ANAK - Friska Novianti; Meryam Bura; Sarma Sitorus; Limbong, Limbong; Mariam Massang (EDUCATIONAL JOURNAL : General and Specific Research, 2024)
This research aims to explore the role played by families in shaping Christian identity in children. Religious identity is acquired through complex interactions between individuals and the family environment. In this context, the study focuses on how Christian values, beliefs, and practices are transmitted and internalized within the family environment. Qualitative research methods were employed, including a case study conducted within the researcher's surroundings, as well as a literature review on relevant topics. Christian families with primary school-aged children were selected as research subjects using a purposive sampling approach. Data were then analyzed using a thematic analysis approach. Initial findings indicate that the role of parents in setting examples, educating, and celebrating religious activities has a significant impact on the formation of Christian identity in children. Religious habits within the family, including communal prayer and participation in church worship, also play a crucial role in solidifying religious identity. Social environmental factors, particularly family involvement in religious communities and Christian religious education, enrich the religious experiences of children. However, challenges such as the influence of secular environments and cultural changes also play a role in the dynamics of Christian identity formation. The results of this research are expected to provide a deeper understanding of the complexity of interactions between families and the Christian identity of children. The implications of this research may contribute to the development of Christian religious education programs and provide guidance for Christian families in guiding their children towards a steadfast religious identity.